2011
DOI: 10.1007/s00125-011-2317-z
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide decreases hepatic fibroblast growth factor 21 resistance in non-alcoholic fatty liver disease in a mouse model of obesity and in a randomised controlled trial

Abstract: Aims/hypothesis Systemic fibroblast growth factor (FGF)21 levels and hepatic FGF21 production are increased in non-alcoholic fatty liver disease patients, suggesting FGF21 resistance. We examined the effects of exenatide on FGF21 in patients with type 2 diabetes and in a diet-induced mouse model of obesity (DIO). Methods Type 2 diabetes mellitus patients (n=24) on diet and/or metformin were randomised (using a table of random numbers) to receive additional treatment consisting of pioglitazone 45 mg/day or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 20 publications
5
62
0
Order By: Relevance
“…Dissimilar results regarding the effect of exendin-4 on FGF21 expression have also been reported. Hepatic FGF21 expression and serum FGF21 levels were decreased in HFD-fed mice treated with exendin-4 for 4 weeks compared to saline treatment (Samson et al 2011). Consistent with this result, the addition of exenatide reduced FGF21 levels in T2D subjects undergoing pioglitazone treatment (Samson et al 2011).…”
Section: Glucagon Glp1 and Fgf21supporting
confidence: 74%
See 1 more Smart Citation
“…Dissimilar results regarding the effect of exendin-4 on FGF21 expression have also been reported. Hepatic FGF21 expression and serum FGF21 levels were decreased in HFD-fed mice treated with exendin-4 for 4 weeks compared to saline treatment (Samson et al 2011). Consistent with this result, the addition of exenatide reduced FGF21 levels in T2D subjects undergoing pioglitazone treatment (Samson et al 2011).…”
Section: Glucagon Glp1 and Fgf21supporting
confidence: 74%
“…Hepatic FGF21 expression and serum FGF21 levels were decreased in HFD-fed mice treated with exendin-4 for 4 weeks compared to saline treatment (Samson et al 2011). Consistent with this result, the addition of exenatide reduced FGF21 levels in T2D subjects undergoing pioglitazone treatment (Samson et al 2011). Furthermore, a decrease in hepatic FGF21 levels was correlated with reduction in hepatic TG content and liver weight in HFD-fed mice after exendin-4 treatment, implying that reduction of FGF21 due to exendin-4 may be secondary to reduced lipid accumulation.…”
Section: Glucagon Glp1 and Fgf21mentioning
confidence: 92%
“…Exendin-4 induced phosphorylation of AMPK, which reduced weight gain and insulin resistance in mice with high-fat diets [16]. Additionally, phosphorylated AMPK was down-regulated in the kidneys of db/db mice [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…However, her level of FGF21 after glycemic treatment was significantly decreased to the level under the threshold of a diagnosis of mitochondrial diseases according to a previous study . As for the influence of glycemic treatment on FGF21 levels in type 2 diabetes patients, FGF21 levels decreased after starting glycemic therapies including insulin (Yang et al 2011) or exenatide, a GLP-1 receptor agonist (Samson et al 2011), although no similar studies in mitochondrial diabetes patients were reported. Therefore, the results of FGF21 in WBC, white blood cell count; RBC, red blood cell count; ALB, serum albumin; T-bil, total bilirubin; AST, aspartate aminotranferase; ALT, alanine aminotranferase; CK, creatine kinase; BUN, blood urea nitrogen; TSH, thyroid stimulating hormone; FGF21, fibroblast growth factor 21; GDF15, growth differentiation factor 15; HbA1c, hemoglobin A1c; anti-GAD, anti-glutamic acid decarboxylase antibody; Anti-IA2, anti-insulinoma antigen 2 antibody.…”
Section: Discussionmentioning
confidence: 99%